2013
DOI: 10.1371/journal.pone.0083103
|View full text |Cite
|
Sign up to set email alerts
|

Rice Performance and Water Use Efficiency under Plastic Mulching with Drip Irrigation

Abstract: Plastic mulching with drip irrigation is a new water-saving rice cultivation technology, but little is known on its productivity and water-saving capacity. This study aimed to assess the production potential, performance, and water use efficiency (WUE) of rice under plastic mulching with drip irrigation. Field experiments were conducted over 2 years with two rice cultivars under different cultivation systems: conventional flooding (CF), non-flooded irrigation incorporating plastic mulching with furrow irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 35 publications
4
41
0
Order By: Relevance
“…In this study, the effects of plant density between non-flooded culture (direct-seeding technology) and flooded culture (1.2 : 1) were ignored, which results were also clarified by our previous studies (He et al, 2013). The study aims at (a) comparing the growth characteristics of all plant organs (including aboveground and underground parts) grown under DI, furrow irrigation with plastic mulching (FIM or called as GCRPSs system) and furrow irrigation with non-mulching (FIN or named 'aerobic rice' system) under non-flooded conditions and (b) determining the optimum irrigation scheme for high grain yield under DI.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In this study, the effects of plant density between non-flooded culture (direct-seeding technology) and flooded culture (1.2 : 1) were ignored, which results were also clarified by our previous studies (He et al, 2013). The study aims at (a) comparing the growth characteristics of all plant organs (including aboveground and underground parts) grown under DI, furrow irrigation with plastic mulching (FIM or called as GCRPSs system) and furrow irrigation with non-mulching (FIN or named 'aerobic rice' system) under non-flooded conditions and (b) determining the optimum irrigation scheme for high grain yield under DI.…”
Section: Introductionmentioning
confidence: 58%
“…Although yield and water use efficiency (WUE) were higher in the DI treatment than in the GCRPSs and 'aerobic rice' treatments when soil water potential in the 0-20 cm depth was maintained between 0 and −30 KPa, grain yield in the DI treatment was still significantly less than that in the traditional flood irrigation treatment (He et al, 2013(He et al, , 2014. Therefore, it is important to diminish the yield gap between DI and flood-irrigated rice in arid region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drip irrigation treatment had more effective tillers, more roots in topsoil, higher WUE, and greater economic benefit in rice (He, Ma, Yang, Chen, & Jia, 2013), but less yield compare with conventional flooding irrigation. Drip irrigation maintained a competitive grain yield and water productivity, and greatly reduced pollution risk to the environment.…”
Section: Introductionmentioning
confidence: 95%
“…Correlation analysis showed that the roots at the a1 and b1 sites were positively significantly correlated with yield components and aboveground agronomic traits. Therefore, improving root development at the a1 and b1 sites at flowering stage could be a key factor to obtain higher grain yield and good agronomic performance under plastic mulching drip irrigation (He et al, 2013). The experiment demonstrates that the di treatment has greater water saving capacity and lower yield and economic benefit gaps than the fim and fin treatments compared with the cf treatment, and would therefore be a better water-saving technology in areas of water scarcity (He et al, 2015).…”
Section: Introductionmentioning
confidence: 99%